Sensitive determination of Amaranth in drinks by highly dispersed CNT in graphene oxide "water" with the aid of small amounts of ionic liquid. (15th July 2015) - Wang, Meiling; Sun, Yinlu; Yang, Xiongbo; Zhao, Jianwei
Highlights: A new graphene oxide-ionic liquid water-based system was developed. A new composite of CNT/GO-[BMIM][PF6 ] with high dispersibility and strong conductivity was presented. The CNT/GO-[BMIM][PF6 ] composite was employed in the sensitive determination of Amaranth. This sensor exhibits lower detection limit for Amaranth (1.0 × 10 −10  M). Abstract: Graphene oxide (GO) is a pH-dependent amphiphile. In this paper, it was found that carbon nanotubes (CNTs) can be highly dispersed in graphene oxide "water" with the aid of prototype ionic liquid of 1-butyl-3-methylimidazolium hexafluorophosphate ([BMIM][PF6 ]). The introduction of [BMIM][PF6 ] not only can minimize the defects of poor electrical conductivity of GO, but also can improve the dispersibility of CNT in water. Hence, a new composite of CNT/GO-[BMIM][PF6 ] with high dispersibility and strong conductivity was presented for the first time and employed in the sensitive determination of Amaranth in soft drinks. The detection limit achieved (0.1 nM) is much lower than the guideline values in soft drinks. The ease of preparation, low background current, high sensitivity and stability can create novel avenues and applications for fabricating robust sensors for determination of other azo dyes in foods.